Metal concentration at surface water using multivariate analysis and human health risk assessment - Azaman, F.; Juahir, H.; Yunus, Kamaruzzaman; Azid, A.; Khalit, S. I.; Mustafa, A. D.; Amran, M. A.; Hasnam, C. N. C; Abidin, M. Z. A. Z.; Yusri, M. A. M. (University of El Oued, Algeria, 2017)
This study defined the concentration of metals in Kerteh and Paka River water and their potential health risk towards human. 54 water samples were collected and analyzed using ICP-OES. Results revealed that most of the stations in Kerteh River gave the higher concentration of Cd, Cu, Zn, Co, Ni, As, Cr and Pb compared to Paka River. However As, Cr and Pb have exceeded the permissible limit of Malaysia standard for all stations in both rivers. Cd, Cu, Zn, Co and Ni were below than Malaysian standard permissible levels during the sampling period. The principal component analysis (PCA) revealed that both geogenic and anthropogenic sources were responsible to possible metals contamination in both rivers. Moreover, risk assessments for all metals were within the safe limits, except for As in the Kerteh River for both adult and child as well as to Paka River for both genders.